E-Layanan Publik Kelurahan 35 Ilir Berbasis Mobile Web - Kiki Rizky Amanda; Muhammad Ariandi; Suyanto; Marlindawati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The rapid advancement of information technology has significantly impacted productivity, enabling tasks to be completed more efficiently. In government and public service institutions, utilizing information technology is essential, as it has proven to enhance the quality of services, making them more responsive, effective, efficient, and accountable. According to Law Number 25, Article 1, Paragraph 1 of 2009, public service is defined as activities or a series of activities aimed at fulfilling service needs based on regulations, for every citizen and resident, concerning goods, services, and/or administrative assistance provided by public service providers. Implementing electronic services accelerates the development of e-Government. Public services at the village administration level play a crucial role in delivering quality service to the community. Unfortunately, public services at the 35 Ilir Village have received numerous complaints from the local community. This issue arises because the administrative document submission system is still handled manually, requiring each document to be printed and filed manually.